The other woman - Ryan, Hank Phillippi (Ryan, Hank Phillippi. Jane Ryland novel., 2012)
Tracking down a candidate's secret mistress days before a pivotal Senate election, reporter Jane Ryland discovers links between her story and a serial killer investigation by detective Jake Brogan, with whom she partners to stop a killer in the face of dirty politics and betrayal.